2021
DOI: 10.1055/s-0041-1726084
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Analysis of Bone Deformities of the Distal Femur in Toy Poodles with Medial Patellar Luxation

Abstract: Objective The aim of this study was to evaluate the bone deformities of the distal femur of Toy Poodles with medial patellar luxation (MPL) using computed tomography. Methods Computed tomography data from 37 stifles of Toy Poodles (16 normal, 10 grade 2 MPL and 11 grade 4 MPL) were analysed. For trochlear morphology, sulcus angle, medial or lateral trochlear inclination and trochlear angle were compared. For condylar morphology, distance between the apex of the medial or lateral trochlear ridge and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…We accept our first hypothesis, as in this study the overall FTGA in dogs without MPL was smaller compared to MPL dogs, similarly to what other authors have recently reported. 8,14,15 Among SB and MLB populations, we discovered a mean FTGA of 128 ± 4.7 in SB and 119 ± 5.6 in MLB with cutoff values of 134 and 128 respectively. These data slightly differ from human literature, which suggests that a normal trochlea has an average sulcus angle of 138 ± 6 , while dysplastic trochleae have a sulcus angle >145 .…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…We accept our first hypothesis, as in this study the overall FTGA in dogs without MPL was smaller compared to MPL dogs, similarly to what other authors have recently reported. 8,14,15 Among SB and MLB populations, we discovered a mean FTGA of 128 ± 4.7 in SB and 119 ± 5.6 in MLB with cutoff values of 134 and 128 respectively. These data slightly differ from human literature, which suggests that a normal trochlea has an average sulcus angle of 138 ± 6 , while dysplastic trochleae have a sulcus angle >145 .…”
Section: Discussionmentioning
confidence: 86%
“…11,12 The benefits of the broad availability of radiographs and ease for performing a skyline view of the femoral trochlea are counteracted by the threedimensional complexity of the trochlea morphology, which changes in proximodistal direction. 7,14,15 Moreover, from the authors' perspective, when performing the skyline radiographic projection, it is difficult to select and analyze one specific point of the trochlear groove. As a result, it would be necessary to perform multiple radiographs with a different degree of stifle flexion, although this will probably increase the sedation time and costs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited data are available on femoral condylar morphology, despite morphological studies in medium to large breed dogs, and in small breeds. 23 26 27 28 29 A trend to a more “vertically” oriented trochlea was noted in small breeds with medial patellar luxation. 23 Visually, many of our small breed dogs had “hockey-stick”-shaped distal femora and a relatively large radius to the trochlear arc, resulting in placement of the best-fit centre caudal to the metaphysis.…”
Section: Discussionmentioning
confidence: 94%